Recovery of Palm Carotene from Palm Oil and Hydrolysed Palm Oil Using Adsorption Column Chromatography - Ling, You Li (2006)
Crude palm oil (CPO) and crude palm olein (CPOlein) were hydrolysed with lipase from Candida Rugosa to produce free fatty acids (FFAs)- rich oil. The palm oil and hydrolysed palm oil were subsequently subjected to column chromatography process. Diaion HP-20 adsorbent was used for reverse phase column chromatography and the column temperature was kept at 50°C. Isopropanol (IPA) or ethanol (EtOH), and n-hexane were used as the first and second eluting solvents, respectively. The objective of hydrolysing the palm oil was to produce more polar FFA-rich oil in order to enhance the non-polar carotene to adsorb to the non-polar HP-20 adsorbent in the column chromatography. The results obtained showed that by hydrolysing CPO and CPOlein with lipase from Candida rugosa, gave 30- and 60-fold, respectively, of FFA production in the crude palm oil and crude palm olein in 8 h at 50°C. For column chromatographic process, using isopropanol or ethanol as the first eluting solvent, crude oil and hydrolysed oil showed the carotene recovery in fraction two (carotene-rich fraction) were about 36-37 and 90-96%, respectively. Over 90% of carotene recovery was obtained from hydrolysed palm oil reflecting an increase of about 55% over CPO. Response Surface Methodology (RSM) for optimisation of carotene recovery from hydrolysed palm olein (HCPOlein) in adsorption chromatography was carried out. The level and interaction of three independent variables was investigated: column temperature (50 to 60°C), oil loading (25 to 200 g), and mobile phase flow rate (6 to 60 mL/min) was investigated. Based on the response as percentage of carotene recovery from 50 g of HP-20 adsorbent, the optimum conditions were achieved at 200 g of oil loading, column temperature at 55°C, and flow rate at 33 mL/min. Up to 98% of carotene recovery was able to obtain under this condition. Interaction of oil-oil and oil-flow rate could enhance percentage of carotene recovery. On the other hand, oil and flow rate as single factors could significantly reduce percentage of carotene recovery. Oil loading as a single factor could positively influence amount of carotene adsorbed. However, flow rate as a single factor and oil-oil interaction could negatively influence amount of carotene adsorbed. The predicted results according to the model for both responses were closed to the observed responses for experiments. The mean of difference (MD) of the experimental and predicted data for percentage of carotene recovery, and amount of carotene adsorbed were very small, - 0.0067 and 0.0133, respectively. The probability (P) value showed no significant lackof- fit for both equations of this model. Laboratory-scale batch studies were carried out to investigate the use of synthetic polymer adsorbent, HP-20, for carotene extraction from CPOlein and HCPOlein. The adsorption of carotene was determined by several adsorption isotherm models such as Langmuir, Freundlich and Scatchard plots. The effect of temperature, contact time, adsobate concentration and the adsorbent mass were examined. The equilibrium data fitted with both Langmuir and Freundlich models with correlation coefficients >0.9.e concentration and the adsorbent mass were